Bafilomycin A1 Attenuates Osteoclast Acidification and Formation, Accompanied by Increased Levels of SQSTM1/p62 Protein. Issue 6 (26th November 2015) - Zhu, Sipin; Rea, Sarah L.; Cheng, Taksum; Feng, Hao Tian; Walsh, John P.; Ratajczak, Thomas; Tickner, Jennifer; Pavlos, Nathan; Xu, Hua‐Zi; Xu, Jiake
ABSTRACT: Vacuolar proton pump H + ‐adenosine triphosphatases (V‐ATPases) play an important role in osteoclast function. Further understanding of the cellular and molecular mechanisms of V‐ATPase inhibition is vital for the development of anti‐resorptive drugs specifically targeting osteoclast V‐ATPases. In this study, we observed that bafilomycin A1, a naturally‐occurring inhibitor of V‐ATPases, increased the protein level of SQSTM1/p62, a known negative regulator of osteoclast formation. Consistently, we found that bafilomycin A1 diminishes the intracellular accumulation of the acidotropic probe lysotracker in osteoclast‐like cells; indicative of reduced acidification. Further, bafilomycin A1 inhibits osteoclast formation with attenuation of cell fusion and multi‐nucleation of osteoclast‐like cells during osteoclast differentiation. Taken together, these data indicate that bafilomycin A1 attenuates osteoclast differentiation in part via increased levels of SQSTM1/p62 protein, providing further mechanistic insight into the effect of V‐ATPase inhibition in osteoclasts. J. Cell. Biochem. 117: 1464–1470, 2016. © 2015 Wiley Periodicals, Inc.